PARP inhibitor Olaparib overcomes Sorafenib resistance through reshaping the pluripotent transcriptome in hepatocellular carcinoma - Xiao-Dong Yang (Molecular Cancer, 2021)
Abstract Hepatocellular carcinoma (HCC) is one of the most common human malignancies worldwide with very poor prognosis. Resistance to targeted therapeutic drugs such as sorafenib remains one of the major challenges in clinical treatment. In the present study, PARP1 was found to be highly expressed in human embryonic stem cells, but progressively decreased upon specified hepatic differentiation. Reactivation of PARP1 expression was also detected in HCC residual tumors after sorafenib treatment in xenograft mouse model, indicating the potential important roles of PARP1 in stem cell pluripotency and HCC sorafenib treatment resistance. Overexpression of PARP1 was frequently observed in HCC patients, and closely associated with poor clinical outcome. Treatment of Sorafenib induced activation of DNA damage repair signaling, which is highly active and essential for maintenance of stem cell pluripotency in HCC residual tumors. PARP inhibitor Olaparib extensively suppressed the DNA damage repair signaling, and significantly inhibited the global pluripotent transcriptional network. The repression of key pluripotent transcriptional factors and DNA damage repair signaling by Olaparib was mainly through CHD1L-mediated condensation of the chromatin structure at their promotor regions. The global reshaping of the pluripotent transcriptome by Olaparib might reinforce Sorafenib in eliminating HCC residual tumors and enhance therapeutic efficiency.